Safe and cost-effective treatment response monitoring of MDR pulmonary tuberculosis by using micro colony broth culture method. (March 2015) - Irfan, S.; Jabeen, K.; Irfan, M.; Rao, N.A.; Azizullah, Z.; Hasan, R.
Abstract: Aims and objectives: Multidrug resistant tuberculosis (MDR-TB) management is expensive, prolonged and complicated. After starting anti-tuberculous treatment in MDR-TB patients, microbiological response to therapy is monitored by monthly sputum cultures. Conventional culture methods are costly, leading to poor compliance with this recommendation in resource-limited settings and reliance on less sensitive sputum microscopy. Published data suggests a less favorable outcome with sputum microscopy and stresses upon use of follow-up cultures. Micro-colony liquid culture method is an established method for diagnosis of new TB cases. As anti- tuberculous treatment may produce considerable changes in bacterial morphology, leading to pleomorphic shapes and sizes, the utility of micro colony broth culture for treatment follow-up cases is uncertain. Therefore, this study aims to evaluate the micro-colony liquid culture method in terms of its sensitivity, specificity, rapidity and cost to monitor response to second-line ATT in diagnosed MDR-TB patients. Methods: Prospective cross-sectional study performed at Clinical Microbiology Laboratory of Aga Khan University. During the period of February 2013–September 2014, a total of 139 adult, MDR-pulmonary TB patients were enrolled in this study. For each patient an appropriate sputum specimen was collected for MTB culture initially and then monthly (maximum) up to the next 6 months. Samples were processed using the standard protocol for microscopy, routine MIGIT & LJ culture and micro colony broth culture method. Micro colony broth culture finally evaluated for sensitivity, specificity, rapidity, cost and contamination rate. Results: To date, a total of 502 sputum samples were submitted from 139 enrolled patients. Out of these, 170 were smear-positive, while 310 were smear-negative. Sensitivity, specificity, positive predictive value and negative predictive value of micro colony broth culture for AFB smear positive samples were 100% (95% CI: 97.83–100), 95.45% (95% CI: 77.08–99.24), 99.42% (95% CI: 96.77–99.90), and 100.00% (95% CI: 83.75–100.00), respectively. Sensitivity, specificity, positive predictive value and negative predictive value of micro colony broth culture for AFB smear negative samples was 100.00% (95% CI: 93.78–100.00), 99.60% (95% CI: 97.80–99.93), 98.31% (95% CI: 90.88–99.72) and 100.00% (95% CI: 98.53–100.00), respectively. Average time of positivity of standard cultures for smear positive samples ( n = 192) was 26.0 days, while micro colony broth culture average positivity time was 8.8 days. Average time of positivity of standard cultures for smear negative samples ( n = 310) was 30.0 days, while micro colony broth culture average positivity time was 11.4 days. Average contamination rate of micro colony broth culture was 4.5% in comparison with 6.1% of routine cultures. Finally, the cost of the micro colony methods was about 35% of the combined BACTEC and LJ media cultures. Conclusions: The preliminary data from this study indicates micro colony broth culture method for MTB detection to be highly sensitive, specific, rapid and cost-effective for treatment monitoring of MDR-TB cases. In resource-limited settings this method can be used safely either alone or along with LJ medium for monitoring of second-line anti-tuberculous treatment. Acknowledgement: This work was supported by a grant from Aga Khan University Research Council.